Latest Advances on Bacterial Cellulose‐Based Materials for Wound Healing, Delivery Systems, and Tissue Engineering. Issue 12 (17th September 2019) - Carvalho, Tiago; Guedes, Gabriela; Sousa, Filipa L.; Freire, Carmen S. R.; Santos, Hélder A.
Abstract: Bacterial cellulose (BC) is a nanocellulose form produced by some nonpathogenic bacteria. BC presents unique physical, chemical, and biological properties that make it a very versatile material and has found application in several fields, namely in food industry, cosmetics, and biomedicine. This review overviews the latest state‐of‐the‐art usage of BC on three important areas of the biomedical field, namely delivery systems, wound dressing and healing materials, and tissue engineering for regenerative medicine. BC will be reviewed as a promising biopolymer for the design and development of innovative materials for the mentioned applications. Overall, BC is shown to be an effective and versatile carrier for delivery systems, a safe and multicustomizable patch or graft for wound dressing and healing applications, and a material that can be further tuned to better adjust for each tissue engineering application, by using different methods. Abstract : This review overviews the latest state of‐the‐art usage of bacterial cellulose (BC) on three important areas of the biomedical fields: delivery systems, wound‐dressing and ‐healing materials, and tissue engineering for regenerative medicine. For these fields, respectively, BC is shown to be an effective and versatile carrier, a safe and multicustomizable patch or graft, and can be fine‐tuned for each application. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visit www.afob.org.